Effects of excess nitrogen on carbohydrate concentration and mycorrhizal development of Pinus sylvestris L. seedlings - Wallander, H; Nylund, J.E (The New phytologist, 1991)
The interaction of nitrogen supply, carbohydrate availability and ectomycorrhiza has been the subject of several studies and has been interpreted as the regulatory mechanism of the symbiosis. Only a few studies have simultaneously examined the effect of external nitrogen supply on the internal concentration of N, the internal sugar pool and, in a quantitative way, the extent of mycorrhizal colonization. The latter has usually been estimated with low accuracy through root tip counting only. Using ergosterol as a quantitative descriptor of fungal biomass, several of the basic assumptions of the carbohydrate theory have been re examined in a semi-hydroponic cultivation system, where Scots pine seedlings mycorrhizal with Laccaria bicolor (Maire) Orton were grown at an approximately constant relative growth rate on a nutrition regime based on a balanced basic medium supplemented with excess ammonium or nitrate. Mycorrhizal biomass was strongly correlated with the shoot nitrogen. High nitrogen availability did not significantly affect internal sugar concentrations. The development of mycorrhiza significantly reduced sugar concentrations in both roots and shoots. The difference between ammonium and nitrate in reducing mycorrhizal development was due to differences in uptake alone. The findings tend to invalidate a basic assumption of the carbohydrate theory, that of high nitrogen availability leading to reduced sugar concentration, the latter limiting mycorrhizal development. The results also conflict with the view that the host's sugar concentration is elevated in the presence of mycorrhiza.